Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Discover solutions to your questions from experienced professionals across multiple fields on our comprehensive Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Answer:
[tex]y = \frac{1}{2}e^x -\frac{1}{2} e^{2-x}[/tex]
Step-by-step explanation:
Given
[tex]y=c_1e^x +c_2e^{-x[/tex]
[tex]y(1) = 0[/tex]
[tex]y'(1) =e[/tex]
Required
The solution
Differentiate [tex]y=c_1e^x +c_2e^{-x[/tex]
[tex]y' = c_1e^x - c_2e^{-x}[/tex]
Next, we solve for c1 and c2
[tex]y(1) = 0[/tex] implies that; x = 1 and y = 0
So, we have:
[tex]y=c_1e^x +c_2e^{-x[/tex]
[tex]0 = c_1 * e^1 + c_2 * e^{-1}[/tex]
[tex]0 = c_1 e + \frac{1}{e}c_2[/tex] --- (1)
[tex]y'(1) =e[/tex] implies that: x = 1 and y' = e
So, we have:
[tex]y' = c_1e^x - c_2e^{-x}[/tex]
[tex]e = c_1 * e^1 - c_2 * e^{-1}[/tex]
[tex]e = c_1 e - \frac{1}{e}c_2[/tex] --- (2)
Add (1) and (2)
[tex]0 + e = c_1e + c_1e + \frac{1}{e}c_2 - \frac{1}{e}c_2[/tex]
[tex]e = 2c_1e[/tex]
Divide both sided by e
[tex]1 = 2c_1[/tex]
Divide both sides by 2
[tex]c_1 = \frac{1}{2}[/tex]
Substitute [tex]c_1 = \frac{1}{2}[/tex] in [tex]0 = c_1 e + \frac{1}{e}c_2[/tex]
[tex]0 = \frac{1}{2} e+ \frac{1}{e}c_2[/tex]
Rewrite as:
[tex]\frac{1}{e}c_2 = -\frac{1}{2} e[/tex]
Multiply both sides by e
[tex]c_2 = -\frac{1}{2} e^2[/tex]
So, we have:
[tex]y=c_1e^x +c_2e^{-x[/tex]
[tex]y = \frac{1}{2}e^x -\frac{1}{2} e^2 * e^{-x}[/tex]
[tex]y = \frac{1}{2}e^x -\frac{1}{2} e^{2-x}[/tex]
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.